The valediction of Moses: a proto-biblical book - Dershowitz, Idan (Forschungen zum Alten Testament, 2021)
"Moses Wilhelm Shapira's infamous Deuteronomy manuscripts -- long believed to be forgeries -- are of far greater significance than ever imagined. Idan Dershowitz shows that the text preserved in these manuscripts is not based on the book of Deuteronomy. On the contrary, it is a proto-biblical book, the likes of which has never before been seen."